Modeling of Diffusion with Partitioning in Stratum Corneum Using a Finite Element Model - Barbero, Ana M.; Frasch, H. F. (Annals of biomedical engineering, 2005)
Partitioning and diffusion of chemicals in skin is of interest to researchers in areas such as transdermal penetration and drug disposition, either for risk assessment or transdermal delivery. In this study a finite element method is used to model diffusion in the skin's outermost layer, the stratum corneum (SC). The SC is considered to be a finite two-dimensional composite having different diffusivity values in each medium as well as a partition coefficient at the interfaces between media. A commercial finite element package with thermal analysis capabilities is selected due to the flexibility of this software to handle irregular geometries. Partitioning is accommodated through a change of variables technique. This technique is validated by comparison of model results with analytical solutions of steady-state flux, transient concentration profiles, and time lag for diffusion in laminates. Two applications are presented. Diffusion is solved in a two-dimensional "brick and mortar" geometry that is a simplification of human stratum corneum, with a partition coefficient between corneocyte and lipid. Results are compared to the diffusion in multiple laminates to examine effects of the partition coefficient. The second application is the modeling of diffusion with partitioning through an irregular geometry which is obtained from a micrograph of hairless mouse stratum corneum.